Exploring the Ion Channel TRPV2 and Testicular Macrophages in Mouse Testis - Eubler Katja; Rantakari Pia; Gerke Heidi; Herrmann Carola; Missel Annika; Schmid Nina; Walenta Lena; Lahiri Shibojyoti; Imhof Axel; Strauss Leena; Poutanen Matti; Mayerhofer Artur (MDPI, 2022)
The cation channel TRPV2 is known to be expressed by murine macrophages and is crucially involved in their functionality. Macrophages are frequent cells of the mouse testis, an immune-privileged and steroid-producing organ. TRPV2 expression by testicular macrophages and possible changes associated with age or inflammation have not been investigated yet. Therefore, we studied testes of young adult and old wild-type (WT) and AROM(+) mice, i.e., transgenic mice overexpressing aromatase. In these animals, inflammatory changes are described in the testis, involving active macrophages, which increase with age. This is associated with impaired spermatogenesis and therefore AROM(+) mice are a model for male infertility associated with sterile inflammation. In WT animals, testicular TRPV2 expression was mapped to interstitial CD206(+) and peritubular MHC II+ macrophages, with higher levels in CD206(+) cells. Expression levels of TRPV2 and most macrophage markers did not increase significantly in old mice, with the exception of CD206. As the number of TRPV2(+) testicular macrophages was relatively small, their possible involvement in testicular functions and in aging in WT mice remains to be further studied. In AROM(+) testis, TRPV2 was readily detected and levels increased significantly with age, together with macrophage markers and TNF-alpha. TRPV2 co-localized with F4/80 in macrophages and further studies showed that TRPV2 is mainly expressed by unusual CD206(+)MHC II+ macrophages, arising in the testis of these animals. Rescue experiments (aromatase inhibitor treatment and crossing with ER alpha KO mice) restored the testicular phenotype and also abolished the elevated expression of TRPV2, macrophage and inflammation markers. This suggests that TRPV2(+) macrophages of the testis are part of an inflammatory cascade initiated by an altered sex hormone balance in AROM(+) mice. The changes in testis are distinct from the described alterations in other organs of AROM(+), such as prostate and spleen. When we monitored TRPV2 levels in another immune-privileged organ, namely the brain, we found that levels of TRPV2 were not elevated in AROM(+) and remained stable during aging. In the adrenal, which similar to the testis produces steroids, we found slight, albeit not significant increases in TRPV2 in both AROM(+) and WT mice, which were associated with age. Thus, the changes in the testis are specific for this organ.